2015
DOI: 10.1038/nclimate2825
|View full text |Cite
|
Sign up to set email alerts
|

Cooling of US Midwest summer temperature extremes from cropland intensification

Abstract: High temperature extremes during the growing season can reduce agricultural production. At the same time, agricultural practices can modify temperatures by altering the surface energy budget. Here we identify centennial trends towards more favourable growing conditions in the US Midwest, including cooler summer temperature extremes and increased precipitation, and investigate the origins of these shifts. Statistically significant correspondence is found between the cooling pattern and trends in cropland intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
198
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(240 citation statements)
references
References 57 publications
21
198
1
Order By: Relevance
“…We also do not consider microclimate feedbacks from irrigation at the Ameriflux station. Although irrigation has been shown in other studies to suppress extreme temperatures in the Midwest (Mueller et al, 2016), we find that the monthly-average temperatures recorded at the Ameriflux Bondville site nearly match the temperature readings at the nearest airport in Champaign, IL (not shown). Also, since the Ameriflux temperatures and SWdn data correspond closely to these value in the 1/8 • NLDAS dataset (Fig.…”
Section: H Cusworth Et Al: Regional Climate In the Central Unitementioning
confidence: 62%
“…We also do not consider microclimate feedbacks from irrigation at the Ameriflux station. Although irrigation has been shown in other studies to suppress extreme temperatures in the Midwest (Mueller et al, 2016), we find that the monthly-average temperatures recorded at the Ameriflux Bondville site nearly match the temperature readings at the nearest airport in Champaign, IL (not shown). Also, since the Ameriflux temperatures and SWdn data correspond closely to these value in the 1/8 • NLDAS dataset (Fig.…”
Section: H Cusworth Et Al: Regional Climate In the Central Unitementioning
confidence: 62%
“…Dense crop canopies and intensely managed agroecosystems have been shown to reduce maximum summertime temperatures in the Corn Belt (i.e. warming hole) to the extent that water is available (Mueller et al, 2015). Therefore, if water becomes more limited in future climates, the ability for maize to regulate summertime temperatures may be inhibited.…”
Section: Ruizmentioning
confidence: 99%
“…Therefore, if water becomes more limited in future climates, the ability for maize to regulate summertime temperatures may be inhibited. Sustained ET associated with biomass sorghum may preserve the observed warming hole in the Midwest, US (Mueller et al, 2015).…”
Section: Ruizmentioning
confidence: 99%
“…The large increase in the area of cropland has increased summer transpiration, which has reduced maximum temperatures in the growing season over the Prairies (Gameda et al, 2007). Other analyses of US Midwest summer temperature maxima also show a cooling from land-use change to cropland (Bonan, 2001) and cropland intensification (Mueller et al, 2016). Figure 5 summarizes the long-term climate impact of the reduction of summer fallow in Saskatchewan (Betts et al, 2013b).…”
Section: Impact Of Land Use On Climatementioning
confidence: 99%
“…Early case studies showed that snow cover reduces surface temperatures by about 5 • C on both the short-term timescale and on monthly timescales (Namias, 1960(Namias, , 1985Cohen and Rind, 1991;Dewey, 1977;Wagner, 1973). However there has been surprisingly little quantitative observational analysis of the impact of snow on local and regional climate.…”
Section: Impact Of Snow Cover On Climatementioning
confidence: 99%